Jesus in Centhini: Embedded Teachings that Cross Spiritual Boundaries - Chandra, Robby Igusti (Interreligious studies and intercultural theology, 2024)
A 19th-century indigenous Javanese literary masterpiece, Serat Centhini, contains Islamic teachings. One of the texts in the multi-volume work describes Jesus as the Son of God, the Word of God, and the Spirit of God who died and was resurrected. Why do its authors describe Jesus in the way most Christians do? Using literary content and contextual analyses, this article shows that Serat Centhini teaches the limitations of human language in talking about God and the need to cross boundaries in spiritual journeys. It also shows that Islam’s reverence for Jesus is more than what most people know, even though Islam remains thoroughly monotheistic. Many faiths can use this article to learn from other spiritual insights while deepening their core faith. It means that Islam and Christians, especially in Indonesia, can cross boundaries and learn from each other while appreciating Javanese indigenous spirituality.